Journal Management at the University of Jambi: An Evaluative Study Towards an Accredited Journal: Journal Management at the University of Jambi: An Evaluative Study Towards an Accredited Journal - Hansein Arif Wijaya; Yusuf, Muhammad; Hendra, Robi (Educational Leadership and Management Journal, 2025)
Scientific journals play a strategic role in ensuring the quality and reputation of higher education institutions, particularly through the national accreditation mechanism facilitated by the Arjuna portal. This study aims to evaluate journal management at the University of Jambi from the aspects of management, substance, accreditation, and indexation as a basis for strengthening governance towards meeting accreditation standards. The study uses a descriptive-evaluative approach with document analysis of the recapitulation file "JURNAL UNJA Rev.xlsx" containing 49 journals as a sample. Data were analyzed quantitatively and descriptively to describe the distribution of Sinta status, ISSN completeness, consistency of publication frequency, the existence of an editorial team and publication ethics, as well as DOAJ and Scopus indexing status. Qualitative-interpretive analysis was conducted by comparing actual conditions with Arjuna standards and literature findings regarding journal management and publication ethics. The results show that the majority of journals in the sample have been Sinta accredited (S1–S6), with the largest concentration in Sinta 4 and Sinta 5, but there are still journals with status 0 and marked "-" which reflect unclear or incomplete accreditation data. Six journals do not yet have an ISSN, five journals show discrepancies in publication frequency, six journals do not have documented editorial team information and publication ethics, and six journals are listed as "empty" or inactive journals. In terms of indexing, only a small number of journals are indexed by DOAJ and two journals are listed in Scopus category Q4. These findings indicate that the University of Jambi has a potential base of accredited journals, but still requires regulatory journal identity, strengthening editorial and ethics institutions, structuring the portfolio of inactive journals, and a gradual strategy for improving accreditation and indexing to support sustainable fulfillment of Arjuna standards.